Regulatory Role of N6-Methyladenosine in Longissimus Dorsi Development in Yak - Ma, Xiaoming; La, Yongfu; Bao, Pengjia; Chu, Min; Guo, Xian; Wu, Xiaoyun; Pei, Jie; Ding, Xuezhi; Liang, Chunnian; Yan, Ping (Frontiers in Veterinary Science, 2022)
The N6-methyladenine (m6A) RNA undergoes epigenetic modification, which is the most extensive intermediate chemical modification in mRNA. Although this modification occurs in all living organisms, it is most widely studied in mammals. However, to date, no study has investigated the m6A transcriptome-wide map of yak and its potential biological functions in muscle development. This study determined the differences in m6A methylation and gene expression during muscle development in yaks belonging to three age groups, namely 3 years (group A), 6 months (group M), and 90-day-old fetuses (group E), by using methylated RNA immunoprecipitation sequencing (MeRIP-Seq) and RNA sequencing (RNA-Seq). In these three groups, a total of 6278 (A), 9298 (E), and 9584 (M) m6A peaks were identified, with their density averaging between 1.02 and 2.01. The m6A peaks were mostly enriched in the stop codon, 3′ UTR region, and inner long exon region with consensus motifs of UGACA. In all the three stages, the m6A peak enrichment level significantly negatively correlated with mRNA abundance (Pearson correlation coefficient r = −0.22 to −0.32, P < 10⁻16). Functional enrichment of genes consistently modified by m6A methylation, particularly those regulating cell differentiation as well as muscle growth and development, was observed at all three stages. Moreover, m6A abundance was negatively associated with gene expression levels, indicating that m6A might play a vital role in modulating gene expression during muscle development in yaks. This comprehensive map thus provides a solid foundation for determining the potential functional role of m6A RNA modification in yak muscle growth.